STRATEGIC DIRECTIONS AND PRIORITIES FOR DEVELOPMENT OF THE TRANSPORT SECTOR OF UKRAINE IN ACCORDANCE WITH THE REQUIREMENTS OF THE WORLD TRADE ORGANIZATION - Pashchenko, Yu. Ye. (Science and Transport Progress, 2008)
In the article the strategic directions and priorities of development of transport sector ofUkraineaccording to the WTO requirements in the sphere of rendering services are considered.